Planning for low carbon mobility: Impacts of transport interventions and location on carbon-based accessibility. (July 2020) - Kinigadner, Julia; Büttner, Benjamin; Wulfhorst, Gebhard; Vale, David
Abstract: Accessibility has been conceptualized and applied in different ways, depending on the underlying political objectives. In the context of climate change and ambitious emission reduction targets, environmental concerns have risen high on the political agenda. Existing methods for assessing transport-related environmental impacts typically depend on realized or modeled travel behavior. Many of them do not entail a spatial dimension, ignore the importance of the land use component, lack scenario building capabilities or have limited communication value. Consequently, accessibility analysis and planning could make a valuable contribution towards a low carbon transition, but needs to attune to the specific objective of reducing transport-related greenhouse gas emissions. This paper introduces a novel conceptualization of location-based accessibility, where CO2 emissions are used as a travel cost in place of time or monetary costs. By identifying and assessing options for interventions in the land use and transport system, carbon-based accessibility instruments might serve a number of potential decision-making purposes related to low carbon mobility planning. Carbon-based accessibility of a business park in the Munich region is analyzed in multiple scenarios to demonstrate the application potential of the method. The experiential application focuses on the effects of changes in vehicle efficiency and occupancy rates of both car and transit, but also compares the resulting carbon-based accessibility levels to alternative sites with the transport system unchanged. Applying carbon-based accessibility instruments to real-world planning issues could enhance strategic decision-making processes in the context of climate change mitigation. Highlights: Accessibility instruments need to be attuned to the challenges of climate change. The proposed method uses CO2 emissions as a travel cost in location-based accessibility measures. The accessibility measure is sensitive to changes in occupancy rate, vehicle efficiency, and electricity generation mix. Carbon-based accessibility might be a useful addition to existing decision-making tools.